THE IMPORTANCE OF ACKNOWLEDGEMENT AS A HIGH CLASS SOCIETY FOR TEENAGER IN ALYSON NOËL’S FAKING 19 - Lisa Novina Santoso; Setefanus Suprajitno (Institute of Research and Community Outreach - Petra Christian University, 2016)
This paper discusses the Alex’s desire to be acknowledged as a high class person. Alex comes from a middle class background. When she enters high school, she started to change. In this paper I analyze the changes that happened to Alex. In the analysis, I use Georg Simmel’s theory about fashion and metropolitan lifestyle. I divided this analysis into three parts. The first part, it discusses what Alex does to get the acknowledgement. Second, it discusses the reasons and result behind her desire to be acknowledged as a high class. Finally, it discusses what Alex learns from her encounter with the high class. Through the analysis I find that Faking 19 shows an important moral lesson. Being acknowledged as a high class is not the most important thing in life. The most important thing in life is when someone can be themselves.